2008
DOI: 10.1038/sj.bjc.6604846
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between hedgehog and epithelial–mesenchymal transition pathways in gastric pit cells and in diffuse-type gastric cancers

Abstract: We previously reported hedgehog (Hh) signal activation in the mucus-secreting pit cell of the stomach and in diffuse-type gastric cancer (GC). Epithelial -mesenchymal transition (EMT) is known to be involved in tumour malignancy. However, little is known about whether and how both signallings cooperatively act in diffuse-type GC. By microarray and reverse transcription -PCR, we investigated the expression of those Hh and EMT signalling molecules in pit cells and in diffuse-type GCs. How both signallings act co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 42 publications
5
87
0
Order By: Relevance
“…In contrast, diffuse-type GC appears in half of all GC cases and is more geographically dispersed. Diffuse-type GC typically develops from H. pylori-free, morphologically normal gastric mucosa without atrophic gastritis, or IM, and is both genetically and phenotypically different from intestinal-type GC (4)(5)(6)(7)(8). Unlike the decreasing incidence of intestinal-type GC, the prevalence of diffuse-type GC is reportedly increasing worldwide.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, diffuse-type GC appears in half of all GC cases and is more geographically dispersed. Diffuse-type GC typically develops from H. pylori-free, morphologically normal gastric mucosa without atrophic gastritis, or IM, and is both genetically and phenotypically different from intestinal-type GC (4)(5)(6)(7)(8). Unlike the decreasing incidence of intestinal-type GC, the prevalence of diffuse-type GC is reportedly increasing worldwide.…”
Section: Introductionmentioning
confidence: 98%
“…MEF2C that are preferentially expressed in diffuse-type GC (7). Thus, the hedgehog-EMT pathway is preferentially activated in diffuse-type GC compared with intestinal-type GC; however, histological typing is currently the only method to distinguish the two major types.…”
Section: Gene Expression Signatures For Identifying Diffuse-type Gastmentioning
confidence: 99%
“…In pancreatic cancer cells, expression of E-cadherin is independent of Snail and Slug but directly regulated by Gli1 [106]. The inhibition of the Hh pathway with cyclopamine, a steroid that blocks SMO, decreases the expression of Gli1 and Gli2, but also the expression of Sip1, Snail2 and Twist2 [107]. Thus, the Hh pathway, through canonical and non-canonical signalling, is involved in the regulation of genes associated with EMT and regulates cell migration.…”
Section: Hedgehog Signallingmentioning
confidence: 99%
“…A previous study investigated differential gene expression profiles of SGC using a cDNA microarray and found that downregulation of E-cadherin and integrin-b4 expression in SGC-derived cell lines was associated with high potential of metastases to the peritoneum and lymph nodes (Hippo et al, 2001), also supporting that induction of EMT-like change by having cell -cell contact with NF-25 fibroblasts may promote cancer aggressiveness, which is probably mediated by the induction of Snail. A recent study by Ohta et al (2009) suggested that EMT may have a pivotal role in the progression and development of SGC; therefore, understanding the mechanism of this EMT-like change in SGC cells is necessary for the development of a novel chemotherapeutic approach against SGC in the future.…”
Section: Sgc Casementioning
confidence: 99%
“…The EMT of cancer cells is often induced by various transcription factors such as Snail, Twist and Slug (Lombaerts et al, 2006), resulting in downregulation of epithelial markers such as E-cadherin and upregulation of mesenchymal markers such as vimentin. In SGC, retained expression of the mesenchymal-like genes induced by hedgehog transcription factor has been reported (Ohta et al, 2009). On the other hand, the balance between local production levels of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases determines the capability of degradation of ECM.…”
mentioning
confidence: 99%